Highly Efficient Conversion of Motor Neuron-Like NSC-34 Cells into Functional Motor Neurons by Prostaglandin E(2) - Nango, Hiroshi (Cells, 2020)
Motor neuron diseases are a group of progressive neurological disorders that degenerate motor neurons. The neuroblastoma × spinal cord hybrid cell line NSC-34 is widely used as an experimental model in studies of motor neuron diseases. However, the differentiation efficiency of NSC-34 cells to neurons is not always sufficient. We have found that prostaglandin E(2) (PGE(2)) induces morphological differentiation in NSC-34 cells. The present study investigated the functional properties of PGE(2)-differentiated NSC-34 cells. Retinoic acid (RA), a widely-used agent inducing cell differentiation, facilitated neuritogenesis, which peaked on day 7, whereas PGE(2)-induced neuritogenesis took only 2 days to reach the same level. Whole-cell patch-clamp recordings showed that the current threshold of PGE(2)-treated cell action potentials was lower than that of RA-treated cells. PGE(2) and RA increased the protein expression levels of neuronal differentiation markers, microtubule-associated protein 2c and synaptophysin, and to the same extent, motor neuron-specific markers HB9 and Islet-1. On the other hand, protein levels of choline acetyltransferase and basal release of acetylcholine in PGE(2)-treated cells were higher than in RA-treated cells. These results suggest that PGE(2) is a rapid and efficient differentiation-inducing factor for the preparation of functionally mature motor neurons from NSC-34 cells.